Meet and Greet with 100 Sabah UMPSA Alumni - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KOTA KINABALU, 16 September 2023 - The Centre for Alumni Relations, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently hosted a Greet & Meet Ceremony with Sabah Alumni at The Pacific Sutera Hotel, Kota Kinabalu.